1997
DOI: 10.1021/ic970023n
|View full text |Cite
|
Sign up to set email alerts
|

An Azide-Bridged Copper(II) Ferromagnetic Chain Compound Exhibiting Metamagnetic Behavior

Abstract: The one-dimensional chain complex [Cu(2)(&mgr;(2)-1,1-N(3))(2)(&mgr;(2)-1,3-NO(3))(2)(&mgr;(2)-1,3-Me(3)NCH(2)CO(2))(2)](n)() (1) contains three different bridge groups, &mgr;(2)-1,1-azide (end-on), &mgr;(2)-nitrate, and &mgr;(2)-syn,syn-carboxylate, arranged so that the azide and carboxylate groups bridge equatorially and dictate the intrachain magnetic behavior between the copper magnetic orbitals. Variable-temperature magnetic susceptibility studies at low field, and magnetization studies at variable field,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 48 publications
4
71
0
1
Order By: Relevance
“…It is well established that syn-syn carboxylate bridge always propagates antiferromagnetic coupling [12][13][14][15], and the aqua bridge has also been suggested to be an antiferromagnetic mediator with an M-O-M angle larger than 93.5°(the magic angle) [49,60] (this angle in the (COO) 2 (H 2 O) triple bridge is in the range 108°-120°). The ferromagnetic coupling for Ni(II) have been qualitatively justified by considering the orbital countercomplementarity between the dissimilar aqua and carboxylate bridges [49,[61][62][63][64][65], and the antiferromagnetic coupling for Mn(II) and Co(II) has been assumed to be due to the increase of net orbital overlap as the number of relevant magnetic orbitals increases [49]. These considerations are supported by our present series of Fe(II), Co(II) and Ni(II) compounds.…”
Section: Magnetic Propertiessupporting
confidence: 68%
“…It is well established that syn-syn carboxylate bridge always propagates antiferromagnetic coupling [12][13][14][15], and the aqua bridge has also been suggested to be an antiferromagnetic mediator with an M-O-M angle larger than 93.5°(the magic angle) [49,60] (this angle in the (COO) 2 (H 2 O) triple bridge is in the range 108°-120°). The ferromagnetic coupling for Ni(II) have been qualitatively justified by considering the orbital countercomplementarity between the dissimilar aqua and carboxylate bridges [49,[61][62][63][64][65], and the antiferromagnetic coupling for Mn(II) and Co(II) has been assumed to be due to the increase of net orbital overlap as the number of relevant magnetic orbitals increases [49]. These considerations are supported by our present series of Fe(II), Co(II) and Ni(II) compounds.…”
Section: Magnetic Propertiessupporting
confidence: 68%
“…The coupling would then be ferromagnetic (or antiferromagnetic) under a given q AO value and antiferromagnetic (or ferromagnetic) above, where q AO is the angle for accidental orthogonality. This phenomenon was observed by Thompson and co-workers for diazine/azide copper complexes, with q AO = 108.58, [14] but it was established by the same group [15] and Escuer et al [16] that the antiferromagnetic nature found for diazine/azide copper complexes for q AO > 108.58 was due to the complementary antibonding overlap phenomenon, [17] and not simply to an effect of an increase of the q 3 ; [8] however, for this compound, the azido ligand is in an axial position, and this lack of magnetic coupling is quite understandable considering that the unpaired electrons of the Cu II centers are localized in the d x 2 Ày 2 orbitals. Our results (i.e.…”
mentioning
confidence: 66%
“…However, that is not the case in 1. 124.3 48 [11] 116.85 65.63 [13] 116.09 69.7 [12] 111.9 75 [24] 108.16 93.10 [13] 107.6 126 [14] 106.7 80±5 [10] 106.6 80 [11] 106.5 126 [14] 105.52 63 [9] 103.0 89 [12] magnetic coupling, not simply the sum of the two separated components [10,21] , and in the reported carboxylato/ EO-azido Cu II systems, all the couplings were ferromagnetic in despite of the Cu-N-Cu angles [13] ( Table 4). The magnetic susceptibilities of 3 were measured on a SQUID magnetometer in the temperature range at 2-300 K. A plot of χ mT vs. T for 3 is shown in Figure 5…”
Section: Articlesmentioning
confidence: 99%